The relationship between knowledge acquisition and knowledge dissemination: Mediating role of ISO 9001 key factors - Nai-Chieh Wei; Yu-Ting Tseng; Shu-Chuan Chen; Chun-Ming Yang (International Journal of Management, Economics and Social Sciences (IJMESS), 2022)
This research aims to examine the impact of ISO 9001 factors on knowledge acquisition and knowledge dissemination to determine the key success elements for organizations. A questionnaire survey method is employed to identify and analyze the relationship between knowledge acquisition, knowledge dissemination, and ISO key factors within organizations. In addition, the research adopts factor analysis to determine key factors of ISO 9001 management system, knowledge acquisition and knowledge dissemination. Moreover, the correlations of these dimensions are examined with correlation analysis and hierarchical regression analysis. The research reveals that the three dimensions (i.e. key factors of ISO 9001, knowledge acquisition, and knowledge dissemination) show significant correlations. Feasible suggestions and corresponding action plans are put forward to provide new directions for knowledge management and serve as a reference for future research. These findings can contribute to promoting knowledge management, revealing behavioral intentions, and providing strategic advice for business operations.
Keywords: A20; A30; 330; Knowledge acquisition; knowledge dissemination; ISO 9001 control system; correlation analysis; regression analysis